Activar la calle. Nombrarse jóvenes en Córdoba, Argentina - Morales, Susana María; Cañete, Alvaro; Manini, Paula (Oficios Terrestres, 2017)
The article explores in the communicative public practices of the collective Jóvenes por Nuestros Derechos developed in the context of the Marcha de la Gorra, held in the city of Córdoba (Córdoba, Argentina), attending to how this practices contribute to the recognizing an the exercise of their condition of citizens in the dispute of the recognition of their condition of young with rights. The notions about youngers of popular sectors on which this organization works are analyzed, through the recognition of their practices, languages, aesthetics and conflicts with security policies to deploy their own communication strategies.